Cloud computing practices and perceived benefits by SMES in Malaysia: some empirical evidence - Hussin, Husnayati; Salleh, Noor Afzan; Suhaimi, Mohd Adam; Md Ali, Asma (IIUM Press, 2019)
The trend of cloud computing adoption is on the rise globally as it offers an attractive option of IT acquisition to organizations. Although similar benefits of cloud services can be gained by SMEs as the larger counterparts, it was reported that cloud computing adoption is still low among SMEs. A similar situation is observed for SMEs in Malaysia despite several initiatives launched by the government. Additionally, not much empirical studies have been conducted in a comprehensive manner to provide insights on the status and practices of cloud adoption among SMEs in Malaysia. Hence, this study is an attempt to fill this gap. Using survey method, a total of 387 responses were used for the descriptive analysis. The findings indicate that most Malaysia small businesses in both service and manufacturing sectors have substantial experience with basic cloud services and adopt similar practices like SMEs in the developed nations. The implication of the findings is that Malaysia SMEs are catching up with the global trend of utilizing cloud computing to improve the competitiveness of their business.